Challenges of Using Portfolio Assessment as an Alternative Assessment Method for Teaching English in Indonesian Schools - Afrianto Afrianto (International Journal of Educational Best Practices, 2017)
Conducting an assessment is a part of teachers' roles and responsibilities. Assessment is a process by which teachers can get feedback for their teaching and students' learning. It can provide data about teachers' teaching effectiveness as well students' learning progress and achievement. Among many alternative authentic assessments suggested in the latest 2013 Curriculum, the portfolio is one of the recommended types of assessment used by teachers at schools lately. However, the reality shows that this portfolio assesment is not used effectively yet in the field. Instead, many teachers still rely on some kinds of traditional tests to assess students' learning. This paper discusses theoretical foundations of this portfolio assessment, followed by a discussion on how to make use of it in the field. Some challenges and possible solutions are also addressed in this paper.